Taking Intellectual Property Rights Seriously: Are We In or Out? (Phase 1: Intellectual Property Awareness Among Students and Faculty: Tracking Changing Attitudes and Awareness) - Tinao, E S; Ibaňez, A D; Rivera, C G; Rivera, A P; Enriquez, C S; de Jesus, A O (KnE Social Sciences, 2018)
The study was conducted to assess the intellectual property awareness among students and faculty was undertaken to determine attitudes, existing IP delivery, drivers seeking information, aspirations, identify unmet needs and generate suggestions to improve the IP system. A mixed method approach using both quantitative and qualitative methodologies were carried out to a prospective group of students and faculty. Data were analyzed and descriptive statistics were used and further analysis using inferential statistics were calculated to compare results. For the students, the most important and relevant topics to the study of Intellectual Property includes knowing where to find and use patent information and the most common method of delivering IP lessons was through briefing workshop on IP, followed by modules and integrating issues in the course. In order to improve IP Delivery, students noted that they prefer to give more emphasis on the overview of IP, patents, copyright, design right and plagiarism. However, students considered that they know some things about Intellectual Property but there were gaps to be filled in. Findings revealed from faculty respondents showed association of the inclusion of the understanding of disclosure and confidentiality to gender, program of students handled by faculty, and cluster where faculty belongs. Moreover, recognition for collaborative work has significant impact on program of students and academic level of faculty. Similarly, other relevant topics like exploiting ideas commercially was found to be associated also with the program of students handled by faculty. Tenure classification was indicated to be associated with understanding health and safety regulations. Results of the focus group discussion with faculty members included improvement of IP delivery and services, curriculum development to include IP education, problems on IP processing, preparation of documents for application. Keywords: intellectual property awareness, IP rights, IP perspectives and insights